Burnout and leadership in special education: A sustainable approach through the Lens of SDG 3 and SDG 4 - Lan Liu; Ke Li; Lulu Yue; Muhammad Zulqarnain Arshad (Acta Psychologica)
Burnout is a critical challenge for special education teachers, undermining teacher well-being and educational quality. This study examines how transformational leadership in special education influences teacher burnout (termed special education work burnout, SEWB) through the mediating pathways of special education teacher admiration and student-centered cognitive empathy (SCCE), and whether these effects depend on teachers' sense of responsibility (SETSR). A quantitative survey was conducted with 439 special education teachers in China. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized model. Results indicated that TLSE is significantly associated with lower burnout, and SETA and SCCE partially mediate this relationship. Teachers who admire their institution and leaders report lower burnout, and those with greater cognitive empathy (better understanding of students' perspectives) also experience reduced burnout, supporting both mediation pathways. TLSE had positive effects on both admiration and cognitive empathy, which in turn diminished burnout levels. Additionally, teachers' sense of responsibility moderated the effects: a strong personal responsibility amplified the beneficial impact of TLSE on cognitive empathy and subsequent burnout reduction. These findings suggest that fostering transformational leadership and empathy can alleviate burnout among special educators. The study contributes to understanding teacher well-being in the Chinese context and aligns with global development priorities (SDG 3: Good Health and Well-Being, SDG 4: Quality Education) by highlighting leadership and professional support as keys to sustainable special education. School administrators should cultivate supportive, visionary leadership and provide resources (including empathy training and digital tools) to reduce teacher stress and promote an inclusive, healthy educational environment.